Graftonite-(Mn), ideally M1MnM2, M3Fe2(PO4)2, and graftonite-(Ca), ideally M1CaM2, M3Fe2(PO4)2, two new minerals of the graftonite group from Poland. (15th May 2018) - Pieczka, Adam; Hawthorne, Frank C.; Ball, Neil; Abdu, Yassir; Gołębiowska, Bożena; Włodek, Adam; Żukrowski, Jan
Abstract: Two new minerals of the graftonite group, graftonite-(Mn), ideally M (1) Mn M (2), M (3) Fe2 (PO4 )2, and graftonite-(Ca), ideally M (1) Ca M (2), M (3) Fe2 (PO4 )2, were discovered in phosphate nodules of two beryl–columbite–phosphate pegmatites at Lutomia and Michałkowa, respectively, in the Góry Sowie Block, Lower Silesia, southwest Poland. Graftonite-(Mn) is pinkish brown, whereas graftonite-(Ca) shows more brownish colouration. Both minerals have a vitreous lustre, a good cleavage observed along (010) and irregular fracture; both are transparent and neither of them is fluorescent. They are brittle and have a Mohs hardness of 5. The minerals are non-pleochroic, colourless in all orientations, biaxial (+), with mean refractive indices α = 1.710(2) and 1.690(2), β = 1.713(2) and 1.692(2), and γ = 1.725(2) and 1.710(5), respectively. With complete order of Ca at the M (1) site, the formulae of the holotype crystals are M (1) (Mn0.70 Ca0.30 ) M (2), M (3) (Fe1.34 Mn0.60 Mg0.06 Zn0.01 )Σ3 (PO4 )2 for graftonite-(Mn) and M (1) (Ca0.98 Mn0.02 ) M (2), M (3) (Fe1.38 Mn0.56 Mg0.05 )Σ3 (PO4 )2 for graftonite-(Ca). Both crystal chemistry and crystal-structure refinement ( R 1 = 2.34 and 1.63%, respectively) indicate that the M (1) site is occupied dominantly by Mn in graftonite-(Mn) and by Ca in graftonite-(Ca), and the M (2) and M (3) sites are occupied by Fe 2+ and Mn 2+, with Fe 2+ dominant over Mn 2+ at the aggregate M (2) + M (3) sites. Graftonite-(Mn) and graftonite-(Ca) are isostructural with graftonite, M (1) Fe M (2), M (3) Fe2 (PO4 )2 (monoclinic system; space-group symmetry P 21 / c ), with the unit-cell parameters a = 8.811(2) Å, b = 11.494(2) Å, c = 6.138(1) Å, β = 99.23(3)° and V = 613.5(4) Å 3, and a = 8.792(2) Å, b = 11.743(2) Å, c = 6.169(1) Å, β = 99.35(3)° and V = 628.5(1) Å 3, respectively. The densities calculated on the basis of molar weights and unit-cell volumes are 3.793 g/cm 3 for graftonite-(Mn) and 3.592 g/cm 3 for graftonite-(Ca). The eight strongest lines in powder X-ray diffraction patterns on the basis of single-crystal data are, respectively [ d, Å, I ( hkl )]: 2.874, 100, (230 + 040); 2.858, 79, (221); 3.506, 73, (130); 2.717, 79, ( 3 11); 2.952, 55, (131); 2.916, 53, ( 1 12); 2.899, 44, (300); 3.016, 35, ( 1 02); and 3.654, 100, (130); 2.979, 85, (221); 3.014, 77, (230); 3.042, 76, (040 + 1 12); 2.834, 68, ( 3 11); 3.097, 57, (131); 3.133, 56, ( 1 02); 2.542, 30, (311). Both minerals are common primary phosphates in phosphate nodules, occurring as lamellar intergrowths with sarcopside ± triphylite/lithiophilite, products of exsolution from a (Li, Ca)-rich graftonite-like parent phase crystallized at high temperature from P-bearing hydrosaline melts.